Naringenin Attenuates Ox-LDL-induced Injury in HUVECs by Regulating Lipophagy Partly through the SOCE Pathway - Jiang, Linhong; Bai, Dandan; Yang, Yunjun; Wu, Yingying; Chen, Yanran; Wang, Mengyuan; Wang, Wenxin; Wang, Haixia; Xiong, Yanzhe; Zhu, Siqi; He, Xinyu; Long, Jun; et al. (Current Pharmaceutical Design, 2025)
ObjectiveNaringenin (NAR) is a naturally occurring tiny molecule that has a significant role in lipid metabolism. However, the molecular mechanism by which NAR is involved in lipid metabolism to protect ECs is not clear. This study aims to investigate the effect of NAR on autophagy in oxidized low-density lipoprotein (ox-LDL)-treated human umbilical vein endothelial cells (HUVECs) and its potential molecular mechanisms.MethodsOxidized LDL-induced HUVECs injury in vitro was treated with NAR. Chloroquine was used as an autophagy inhibitor. Ionomycin (Iono) and 2-aminoethoxydiphenylborate (2-APB) were used as an SOCE pathway agonist and an inhibitor, respectively. The autophagy levels in HUVECs were determined by quantitative real-time PCR, Western blot, and immunofluorescence methods. The concentration of calcium ions in HUVECs was measured by flow cytometry.ResultsThe findings revealed that NAR increased the viability of ox-LDL-impaired HUVECs. NAR increased the level of autophagy and decreased lipid accumulation in ox-LDL-treated HUVECs, which could interfere with chloroquine. Moreover, NAR significantly downregulated the expression of STIM1 and ORAI1 proteins and Ca2+ levels in the SOCE, which could be interfered with Iono or 2-APB, respectively.ConclusionIn summary, NAR can increase autophagy levels and decrease lipid accumulation in HUVECs, eventually protecting against ox-LDL-induced injury in HUVECs, which is associated with inhibition of the SOCE pathway.
Keywords: endothelial cells